2008
DOI: 10.2134/agronj2007.0042
|View full text |Cite
|
Sign up to set email alerts
|

Harvest Techniques Change Annual Warm‐Season Legume Forage Yield and Nutritive Value

Abstract: A gronomy J our n al • Volume 10 0 , I s sue 3 • 2 0 0 8 765 ABSTRACT Comparison among warm-season legume forage trials may not be valid if harvest techniques vary. To address this question, herbage dry matter (DM) yields, branching, crude protein (CP), and fi ber concentrations for nine warm-season annual herbaceous legumes were measured by hand-plucking all leaves and pliable tips or clipping at 7.5-or 15-cm height. Th e experiment was conducted in Texas on a Windthorst fi ne sandy loam over 2 yr. Harvest te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 21 publications
(32 reference statements)
7
24
3
Order By: Relevance
“…The DM yield of these legumes was greater than those values reported under rainfed conditions (7). In this study, lablab and cowpea first cut in 2009 was at 10 weeks (70 DAP) and the second cut was about 7 weeks after first cut (119 DAP), which indicated cowpea may be negatively impacted by multiple harvests (9) or require an extended growing season as reported in other studies (6). Both cowpea cultivars yielded less than the lablab cultivars and there was a difference between cowpea (0.79 and 3.09 Mg/ha for CATJ and I&C, respectively; P < 0.002, SEM = 0.345), but not between lablab cultivars (5.77 and 4.39 Mg/ha for RO and RV, respectively; P > 0.07, SEM = 0.345).…”
Section: Dry Matter Yieldsupporting
confidence: 72%
See 2 more Smart Citations
“…The DM yield of these legumes was greater than those values reported under rainfed conditions (7). In this study, lablab and cowpea first cut in 2009 was at 10 weeks (70 DAP) and the second cut was about 7 weeks after first cut (119 DAP), which indicated cowpea may be negatively impacted by multiple harvests (9) or require an extended growing season as reported in other studies (6). Both cowpea cultivars yielded less than the lablab cultivars and there was a difference between cowpea (0.79 and 3.09 Mg/ha for CATJ and I&C, respectively; P < 0.002, SEM = 0.345), but not between lablab cultivars (5.77 and 4.39 Mg/ha for RO and RV, respectively; P > 0.07, SEM = 0.345).…”
Section: Dry Matter Yieldsupporting
confidence: 72%
“…While cowpea had lower DM yield than lablab, it had greater CP, and NE L concentration, and lower NDF and ADF concentrations than lablab (Table 3). Although cowpea had greater CP, both legumes had > 200 g CP/kg, which is in the upper range of the values reported in other studies (6,9). The NDF concentration was below 350 g/kg in both legumes and was lower than those values reported previously for lablab (3), but ADF and ADL concentrations were in the range of those values reported by for lablab and cowpea (9).…”
Section: Nutritive Valuesupporting
confidence: 55%
See 1 more Smart Citation
“…Muir et al (2008) reported (as crude protein) higher N concentrations, pooled across a series of harvest techniques, for forage cultivars of cowpea and mung bean than we recorded for grain cultivars. The N concentration of shortseason legumes declined during the fi rst half of the season, but increased with the approach of the end of their growing season, as pods developed.…”
Section: Discussioncontrasting
confidence: 41%
“…Annual variations in biomass production by cowpea, mung bean, and soybean in the SGP have been reported (Rao et al, 2005a;Muir et al, 2008). On average, the experimental species did not exceed the level of production generated by soybean, the most commonly used summer legume in the SGP.…”
Section: Discussionmentioning
confidence: 98%